FUNCTIONAL FOOD SUPPORT GOVERNMENT POLICIES TO PREVENT STUNTING - DARWATI SUSILASTUTI; ADITIAMERI ADITIAMERI; LULUK SUTJI MARHAENI (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
Stunting is a chronic nutritional problem in children. The prevalence of stunting in Indonesia in 2019 is still high, namely 27.7%, still far from the WHO standard which should be below 20%. Stunting threatens the productivity of Indonesia's human resources. Overcoming it is part of an effort to protect children. The nutritional status of pregnant women and children under five is a central point in preventing stunting. The mother's knowledge about healthy food and a nutritious, diverse, balanced, and safe diet (B2SA) determines the nutritional intake of the family. This paper is intended to reveal local functional foods that have the potential to produce healthy, healthy food to prevent stunting in the community. This paper is prepared based on a Meta-Analysis of literature studies and community good practices. The incidence of stunting in Indonesia is not caused by food security, indicators of availability and accessibility, but rather by utilization. The utilization of local food diversity, both vegetable and animal, in Indonesia has the potential to be developed into functional food as healthy food to prevent stunting. It takes knowledge, technology, and assistance for the community to develop it.